Characterization of mast cell‐derived rRNA‐containing microvesicles and their inflammatory impact on endothelial cells. Issue 4 (31st January 2019) - Elsemüller, Ann‐Kathrin; Tomalla, Vanessa; Gärtner, Ulrich; Troidl, Kerstin; Jeratsch, Sylvia; Graumann, Johannes; Baal, Nelli; Hackstein, Holger; Lasch, Manuel; Deindl, Elisabeth; Preissner, Klaus T.; Fischer, Silvia
ABSTRACT: Tissue‐resident mast cells (MCs) are well known for their role in inflammatory responses and allergic and anaphylactic reactions, but they also contribute to processes of arterial remodeling. Although ribosomes and cytosolic RNAs are located around secretory granules in mature MCs, their functional role in MC responses remains unexplored. Previous studies by our group characterized extracellular RNA (eRNA) as an inflammatory and pathogenetic factor in vitro and in vivo . In the present study, RNA‐containing MCs and eRNA were located in close proximity to growing collateral arteries in vivo. In vitro, various agonists were found to induce the degranulation of MCs and the concomitant release of eRNA in association with microvesicles (MVs). The liberation of eRNA from MCs was abolished by MC stabilizers or by preventing the increase of intracellular Ca 2+ in MCs. eRNA was found to be mainly contained inside MVs, as demonstrated by electron microscopy and immunocytochemistry. The exposure to and the uptake of MC‐released MVs by cultured endothelial cells increased their expression of cytokines, such as monocyte chemo‐attractant protein or IL‐6, in a dose‐ and time‐dependent manner. These results indicate that RNA‐containing MC‐derived MVs are likely to be involved in inflammatory responses, relevant, for example, to processes of vascular remodeling.—Elsemüller, A.‐K., Tomalla, V., Gärtner, U., Troidl, K., Jeratsch, S., Graumann, J., Baal, N., Hackstein, H., Lasch, M., Deindl, E., Preissner, K. T., Fischer, S. Characterization of mast cell‐derived rRNA‐containing microvesicles and their inflammatory impact on endothelial cells. FASEB J. 33, 5457–5467 (2019). www.fasebj.org